Critical thinking intervention for stress reduction among undergraduates in the Nigerian Universities. Issue 11 (19th March 2021) - Ugwuozor, Felix Okechukwu; Otu, Mkpoikanke Sunday; Mbaji, Isaac Nnamdi
Abstract: Background: The stress level of undergraduates is increasing at an alarming rate. This study's objective was to determine the effect of critical thinking intervention (CTI) for stress reduction among undergraduates in Nigerian Universities. Methods: This research used a pretest-posttest design. Participants were 103 undergraduates who had experienced a high level of stress. The Academic Stress Questionnaire (ASQ) and the Educational Stress Scale (ESSS) were the measures used for data collection in the study, while repeated measures analysis of variance was used for data analysis. Results: Before the intervention, assessment results showed that the stress level of participants was high, with no difference between those undergraduates in the treatment group and those in the no-treatment control group. After the intervention, the assessment results indicated a significant reduction in the undergraduates' stress level in the treatment group compared to those in the no-treatment control group. Further significant reduction was observed in the undergraduates' stress level in the treatment group compared to those in the no-treatment control group after follow-up assessment. Conclusion: The authors concluded that CTI intervention was significantly effective for stress reduction among undergraduates in Nigerian Universities. Therefore, counselors are called upon to adopt the principle of CTI intervention to help patients under stress reduce their stress levels.